I03 The cardiovascular implications for exercise intolerance and dyspnoea in electronic cigarette users - Giles, Agata; Junejo, Rehan; Jones, Sarah; Philips, Olivia; Vadher, Jay; Henthorn, Libby; Morse, Christopher; Faisal, Azmy (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Background: Electronic cigarettes (EC) have been proposed as a safe alternative to tobacco smoking, however, several studies have shown adverse health effects of EC. The chronic implications of EC on cardiorespiratory response and exertional dyspnoea are unknown. Aim: To examine the chronic effects of electronic cigarettes (EC) and tobacco cigarettes (TC) on resting vascular function, inflammatory markers, cardiorespiratory responses during exercise and exertional dyspnoea. Methodology: Three groups of young adults (16 each) with normal spirometry (EC users, TC smokers, and never-smokers [NS]) consented to participate in this study following institutional ethics approval. Participants performed spirometry and an incremental cardiopulmonary exercise test (CPET) 20W/2mins on an electronically braked cycle ergometer with blood lactate (BLa) measurements. Flow-mediated dilation (FMD%) of the brachial artery was assessed using Doppler ultrasonography. Venous blood samples were collected to assess inflammatory biomarkers associated with vascular function. Results: EC and TC groups had a lower peak work rate compared to NS controls (184 ± 30; 185 ± 35 vs. 228 ± 44 W, respectively; P < 0.05). During submaximal exercise, EC and TC groups displayed higher ventilation (VE), higher ratings of dyspnoea and more intense leg fatigue compared to NS controls (e.g. 140 W, VE: 62 ± 10; 64 ± 12 vs. 54 ± 7 L/min, Dyspnoea: 5.0 ± 1.9; 6.1 ± 1.9 vs. 3.4 ± 1.7 Borg units, 6.1 ± 2.05; 7.0 ± 1.9 vs. 4.1 ± 2.1 Borg units, respectively; all P < 0.05). The TC group displayed lower ventilatory efficiency (higher V̇E/V̇CO2) and higher blood lactate compared to NS during submaximal exercise (e.g. 140 W, V̇E/V̇CO2: 31.8 ± 5.6 vs. 28.2 ± 2.41, Blood lactate: 6.5 ± 2.4 vs. 4.3 ± 2.5 mmol/L, respectively; P < 0.05 for both). Like the TC group, the EC group showed a trend for lower ventilatory efficiency and higher BLa during submaximal exercise, but they did not reach statistically significant differences compared to NS controls (P = 0.07 for both). FMD was significantly lower in EC and TC groups compared with NS controls (5.4 ± 2.4; 4.6 ± 2.9 vs. 7.9 ± 3.4%, respectively; P < 0.05) and that was associated with elevated Thrombospondin-1 levels. Conclusion: EC and TC impair vascular function and cardiorespiratory responses to exercise and exertional dyspnoea similarly. EC has a detrimental impact on vascular function and exercise capacity and should not be recommended as a ‘healthier’ alternative to TC.